Effect of post-vitrification cryopreservation duration on singleton birth-weight in frozen-thawed blastocysts transfer cycles - Wang, Xue; Xiao, Yaling; Sun, Zhengyi; Xiong, Wei (Frontiers in Endocrinology, 2024)
Introduction: This study aimed to explore the effect of cryopreservation duration after blastocyst vitrification on the singleton birth-weight of newborns to assess the safety of long-term preservation of frozen–thawed blastocyst transfer (FBT) cycles. Methods: This was a retrospective observational study conducted at the Gynecological Endocrinology and Assisted Reproduction Center of the Peking Union Medical College Hospital. Patients who gave birth to singletons between January 2006 and December 2021 after undergoing FBT cycles were included. Five groups were formed according to the duration of cryopreservation of embryos at FBT: Group Ⅰ included 274 patients with a storage time < 3 months. Group Ⅱ included 607 patients with a storage time of 3–6 months. Group Ⅲ included 322 patients with a storage time of 6–12 months. Group Ⅳ included 190 patients with a storage time of 12–24 months. Group Ⅴ included 118 patients with a storage time of > 24 months. Neonatal outcomes were compared among the groups. Multivariate linear regression analysis was performed to evaluate birth-weights and other birth-related outcomes. Results: A total of 1,511 patients were included in the analysis. The longest cryopreservation period was 12 years. The birth-weights of neonates in the five groups were 3344.1 ± 529.3, 3326.1 ± 565.7, 3260.3 ± 584.1, 3349.9 ± 582.7, and 3296.7 ± 491.9 g, respectively (P > 0.05). The incidences of preterm birth, very preterm birth, low birth-weight, and very low birth-weight were similar in all groups (P > 0.05). The large-for-gestational-age and small-for-gestational-age rates did not differ significantly among the groups (P > 0.05). After adjusting for confounding factors that may affect neonatal outcomes, a trend for an increased risk of low birth-weight with prolonged cryopreservation was observed. However, cryopreservation duration and neonatal birth-weight were not significantly correlated (P > 0.05). Conclusion: The duration of cryopreservation after blastocyst vitrification with an open device for more than 2 years had no significant effect on the birth-weight of FBT singletons; however, attention should be paid to a possible increase in the risk of low birth-weight.